USUAL Watershed Tools: A new geospatial toolkit for hydro-geomorphic delineation. (January 2023) - David, Scott R.; Murphy, Brendan P.; Czuba, Jonathan A.; Ahammad, Muneer; Belmont, Patrick
Abstract: Watershed and hydro-geomorphic delineation is a critical first step in most environmental and natural resource assessments, analyses, and research. While existing geospatial tools have provided exceptional advances, less attention has been put toward developing fully automated tools for subdividing landscapes into their constituent hydro-geomorphic units or discretizing river corridor features. Here, we present a new, open-source ArcGIS toolbox, called the Utah State University AppLied (USUAL) Watershed Tools. The USUAL Tools are a set of streamlined, easy-to-use ArcGIS toolboxes that automate the delineation of watersheds, sub-catchments, river-adjacent interfluves, and discretized river networks with the topological structure and feature attributes necessary for one-dimensional source-to-sink transport modeling through large watersheds. This novel geospatial toolset replaces the need for extensive delineation workflows, providing the Earth science, environmental science, and natural resources communities with the ability to rapidly and easily automate necessary but often time-intensive tasks in a format familiar to ArcGIS users. Highlights: USUAL Watershed Tools has a user-friendly interface that will be familiar to ArcGIS users. USUAL automates manual GIS workflows to delineate watersheds, river networks, sub-catchments, and interfluves. USUAL can handle delineations of either single or nested watersheds. USUAL automates the adjustment of interfluve and sub-catchment delineations around erroneous topography (e.g. waterbodies). USUAL discretizes and attributes river networks with outputs that can feed directly into 1-D network routing models.